International investment agreements in services (UN New YorkUS, 2005)
Reviews the growing importance of services foreign direct investment and its regulation. Provides an overview of services international investment agreements (IIAs), and their evolution over time. Addresses complexities and challenges, particularly as they arise from the overlap between regional and multilateral services IIAs. Deals with the interaction between national and international policies and discusses the need to strike a development-oriented balance.
Keywords: SERVICE INDUSTRY